2022
DOI: 10.3390/antiox11101948
|View full text |Cite
|
Sign up to set email alerts
|

Rosehip (Rosa canina L.) Meal as a Natural Antioxidant on Lipid and Protein Quality and Shelf-Life of Polyunsaturated Fatty Acids Enriched Eggs

Abstract: Eggs are a common food of animal origin, inexpensive, and rich in bioactive substances with high biological value. Eggs enriched in polyunsaturated fatty acids (PUFA) are extremely desired by the progressive consumer. However, during storage, eggs undergo some physiochemical changes, which decrease their value. In this regard, the effect of dietary rosehip meal and flaxseed meal on hens’ egg quality characteristics, amino acids, fatty acids, health-related indices, antioxidant capacity, total polyphenols conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 66 publications
6
17
0
Order By: Relevance
“…At the same time, it is known from the literature data that polyunsaturated fatty acids are easily susceptible to oxidation [ 15 ]. This disadvantage can be minimized by the addition of antioxidant substances that inhibit the unfavorable transformation of these acids [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is known from the literature data that polyunsaturated fatty acids are easily susceptible to oxidation [ 15 ]. This disadvantage can be minimized by the addition of antioxidant substances that inhibit the unfavorable transformation of these acids [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eggs contain low levels of n-3 FA, but the FA profile of egg yolk fats could be improved by adding natural sources of n-3 FA to the diets of hens. Previous reports have shown that table eggs can be enriched with n-3 FA by adding flax seeds [ 2 , 6 , 7 ], hemp seeds [ 8 , 9 , 10 , 11 ], or hemp seed cake [ 11 ] to the diet.…”
Section: Introductionmentioning
confidence: 99%
“…Hemp seed fats are high in PUFAs (78.61% of total FAs), including linoleic acid (54.80%) and α-linolenic acid (18.63%) [ 15 ]. The main reason why hemp seeds could be used in hens’ feed is the relatively high level of ALA (18–19%) [ 15 ], surpassed only by flax seeds (55–57%) [ 6 ]. The introduction of 8% hemp seeds in the diets of laying hens led to enriched omega-3 FAs in egg yolks, specifically ALA, EPA, and DHA [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Linoleic, -linolenic, and oleic fatty acids were the most abundant unsaturated fatty acids in rosehip seed oil [ 14 ]. Due to these reasons, rosehips are used in developing new products in the food and pharmacy industries [ 4 , 15 , 16 , 17 ]. For example, the use of rosehip meal in eggs enriched with polyunsaturated fatty acids had a positive effect on the amino acid and fatty acid content, as well as the antioxidant capacity, and was very effective in extending the shelf-life of eggs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these reasons, rosehips are used in developing new products in the food and pharmacy industries [ 4 , 15 , 16 , 17 ]. For example, the use of rosehip meal in eggs enriched with polyunsaturated fatty acids had a positive effect on the amino acid and fatty acid content, as well as the antioxidant capacity, and was very effective in extending the shelf-life of eggs [ 16 ]. The supplementation of Rosa canina rosehips may be recommended as a natural colourant in poultry diets in conventional or organic egg production [ 17 ].…”
Section: Introductionmentioning
confidence: 99%